Tolerance and volatile flavor substances produced by Millerozyma farinose - ZHANG Xia, LEI Xuejun, WANG Xiaomei, LU Yanping, LI Zhansheng, ZHAO Dong, LI Yuzhu, ZHENG Jia (Zhongguo niangzao)
Using Millerozyma farinose WLY-Y-91 isolated from the brewing environment of strong-flavor (Nongxiangxing) Baijiu as research object, through tolerance and flavor substances metabolism analysis, the adaptation of the strain to the environment of strong-flavor pits were investigated and it was utilized by fermented grains for fermentation. The results showed that M. farinose WLY-Y-91 had good tolerance, it could tolerate 16% ethanol, 200 g/L NaCl and 1 000 g/L glucose, and it could tolerant high temperature of 50 ℃ and pH 2.0. A total of 15 common volatile flavor compounds were detected in YPD and Wuliang powder fermentation broth of strain WLY-Y-91, and 18 characteristic volatile flavor compounds were detected in Wuliang powder fermentation broth, mainly alcohols, esters and ethoin. There were 23 characteristic volatile flavor components detected in YPD fermentation broth of strain WLY-Y-91, which were mainly pyrazines. By simulating Baijiu solid fermentation at laboratory level, it was found that inoculation with strain WLY-Y-91 could reduce the residual starch and residual sugar content in pit-entry fermented grains and surface fermented grains by 25.50%, 76.27%, 20.52% and 90%, respectively. The contents of ethyl acetate, n-propanol and isoamyl alcohol were increased by 143.8%, 20.3%, 132.1% and 44.2%, 13.89%, 32.67%, respectively, indicating that the strain could synthesize ethyl acetate, n-propanol and isoamyl alcohol by utilizing pit-entry fermented grains and spent grains. It had a certain guiding effect on the study of the fermentation of M. farinose in strong-flavor Baijiu pit.